Twisted thinking and its relationship to radical thinking among university students - Mohammed H.T.S. AL-Ogaidi; Yasir M. Al-Dulami (SA Journal of Industrial Psychology)
Orientation: Twisted thinking and its relationship to radical thinking among university students.